The Evolution of Democratization Policy in the Neoconservative Thinking in the Post-Communist World: Factors of Change - Bouguerra, Soumia (Journal of Human Sciences, 2018)
Neoconservatives had always been passionate defenders of American liberal democracy, but their relation to the principle has changed through phases. Basically, Neoconservatives’ changing positions to the principle has moved from just an attachment to a belief to the degree that they had called to its forcible spreading abroad. In the immediate post-communist era their relationship to democracy embodied in the positions they held to ensure the principle efficacy without a serious need to its spreading. A decade later, neoconservatives held that forcible democracy fostering became central to the American foreign policy agenda. To understand the dramatic change in the evolution of democratization policy in the neoconservative thinking, this article argues for three main factors: the unsurpassed position the United States gained following the collapse of bipolarity has helped the emergence of more radical neoconservatives rather than prudent elders, the impact of democracy promotion discourses including Francis Fukuyama’s ‘End of History’ thesis and the democratic peace theory.